NEOTECTONIC OF EAST ANATOLIAN PLATEAU (TURKEY) AND LESSER CAUCASUS: IMPLICATION FOR TRANSITION FROM THRUSTING TO STRIKE-SLIP FAULTING - Koçyiǧit A.; Yilmaz A.; Adamia S.; Kuloshvili S. (My University, 2001)
The east Anatolian plateau and the Lesser Caucasus are characterised and shaped by three major structures: (1) NW- and NE-trending dextral to sinistral active strike-slip faults, (2) N-S to NNW-trending fissures and /or Plio-Quatemary volcanoes, and (3) a 5-km thick, undeformed Plio-Quatemary continental volcanosedimentary sequence accumulated in various strike-slip basins. In contrast to the situation in the east Anatolian plateau and the Lesser Caucasus, the Transcaucasus and the Great Caucasus are characterised by WNW-trending active thrust to reverse faults, folds, and 6-km thick, undeformed (except for the fault-bounded basin margins) continuous Oligocene-Quaternary molassic sequence accumulated in actively developing ramp basins. Hence, the neotectonic regime in the Great Caucasus and the Transcaucasus is compressional-contractional, and Oligocene-Quaternary in age; whereas it is compressional-extensional, and Plio-Quatemary in age in the east Anatolian plateau and the Lesser Caucasus.
Keywords: Oligocene; Quaternary; Кайнозой::Палеоген::Олигоцен; Cenozoic::Quaternary; Cenozoic::Paleogene::Oligocene; Кайнозой::Четвертичная